The Application Of Project-Based Learning (Pjbl) Model Through Series Picture Media As An Improvement Of Narrative Writing Skills Of Grade Iv Elementary School Students - Raharjo, Agung Tri Susilo; Rochmiyati, Siti; Susanto, Moh. Rusnoto (V-art: Journal of Fine Art, 2024)
Implementing Indonesian language learning in elementary schools, educators or teachers certainly have learning models that are suitable to the material to be delivered. This learning model is very important because with the right learning model it will trigger students to be active and creative. The Project Based learning model is a learning model that guides students to increase creativity in learning. The aim of this research is to determine students understanding in learning Indonesian through picture series media to improve the narrative essay writing skills of class IV students in the Indonesian language subject. This study used descriptive qualitative method. Data collection techniques use observation, interview and documentation. This results of the research show that the project Based Learning model is very suitable to apply to increase student creativity in learning Indonesian through the media of picture series. It was proven that out of 28 student, 5 student began to develop, 17 student develop according to expectations, 6 student developed very well. The conclusion is that the innovation conduct by Project Based Learning model through the media of pictures series has a great influence on improving narrative essay writing skills in grade IV elementary school students.